Case report of hemolytic anemia after mitral valve repair - L. V. Pidhaina; S. I. Mohnatiy; O. D. Bablyak; O. M. Dovgan; N. M. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2016)
Hemolytic anemia after mitral valve repair is still an underestimated complication because it is a rare condition and there are few described case reports in the literature. The mechanism responsible for hemolysis most commonly involves a regurgitant jet and it appears to be independent of its severity as assessed by echocardiography. Patients may experience severe symptoms with only moderate regurgitant jets.We present a case of a 66-year-old male who developed severe hemolytic anemia and decompensated heart failure. The aortic valve’ prothesis function was normal.There was a moderate mitral valve regurgitation jet, but it was not considered severe enough to explain such hemolysis. After exclusion of other causes of hemolytic anemia and the lack of clinical and laboratory improvement, the patient underwent mitral valve re-repair. Anemia and heart failure symptoms gradually resolved after surgery.Cardiologists, cardiosurgeons, general practitioners should consider an availability of developmentof hemolytic anemia avter mitral valve repair. Transesophageal echocardiography is an important tool for diagnosis of the problem.